PENGARUH LIKUIDITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN INDEKS LQ45 PERIODE 2015-2019) - Elna M. Pattinaja; Asra Novitasari M (Manis: Jurnal Manajemen dan Bisnis, 2021)
This research was conducted to determine the effect of liquidity projected by current ratio (CR) and dividend policy projected by dividend payout ratio (DPR) on the projected share price with theclosing price of thecompany. The population in this study was the LQ45 index company listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sample in this study was 45 LQ45 index companies listed on the Indonesia Stock Exchange (IDX). The sample determination method used is a purposive sampling method with a sample of 8 companies during a 5-year observation period. The analytical technique used is Multiple Regression Analysis to explain and test hypotheses. The results of this study showed that the Liquidity variable had a negative and significant effect on the Stock Price but the Dividend Policy variable had no significant effect on the Stock Price on the LQ45 index for the period 2015-2019.